N‐methyl‐D‐aspartate receptor dysfunction by unmutated human antibodies against the NR1 subunit. Issue 5 (2nd April 2019) - Wenke, Nina Kerstin; Kreye, Jakob; Andrzejak, Ewa; van Casteren, Adriana; Leubner, Jonas; Murgueitio, Manuela S.; Reincke, S. Momsen; Secker, Christopher; Schmidl, Lars; Geis, Christian; Ackermann, Frauke; Nikolaus, Marc; et al.
Abstract : Anti–N‐methyl‐D‐aspartate receptor (NMDAR) encephalitis is the most common autoimmune encephalitis related to autoantibody‐mediated synaptic dysfunction. Cerebrospinal fluid–derived human monoclonal NR1 autoantibodies showed low numbers of somatic hypermutations or were unmutated. These unexpected germline‐configured antibodies showed weaker binding to the NMDAR than matured antibodies from the same patient. In primary hippocampal neurons, germline NR1 autoantibodies strongly and specifically reduced total and synaptic NMDAR currents in a dose‐ and time‐dependent manner. The findings suggest that functional NMDAR antibodies are part of the human naïve B cell repertoire. Given their effects on synaptic function, they might contribute to a broad spectrum of neuropsychiatric symptoms. Ann Neurol 2019;85:771–776